2009
DOI: 10.1080/14756360802057500
|View full text |Cite
|
Sign up to set email alerts
|

Protein glycation inhibitory activities ofLawsonia inermisand its active principles

Abstract: The protein glycation inhibitory activity of ethanolic extract of Lawsonia inermis (henna) plant tissues was evaluated in vitro using the model system of bovine serum albumin and glucose. Protein oxidation and glycation are posttranslational modifications that are implicated in the pathological development of many age-related disease processes. This study investigated the effects of Lawsonia inermis ethanolic extract and its components, on protein damage induced by a free radical generator in in vitro assay sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 29 publications
0
20
1
3
Order By: Relevance
“…On the other hand, the methanolic extract was effective probably due to the involvement of alkaloids, glycosides, terpenoids and flavonoids. Previously, also Sultana et al (2009) demonstrated that ethanol extract and its components lawsone and gallic acid showed significant protein glycation inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the methanolic extract was effective probably due to the involvement of alkaloids, glycosides, terpenoids and flavonoids. Previously, also Sultana et al (2009) demonstrated that ethanol extract and its components lawsone and gallic acid showed significant protein glycation inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Scheme 28. [198][199][200] This phenolic quinone compound has been evaluated to possess a wide range of biological and pharmacological activities such as antioxidant, 201 antibacterial, 202 antifungal, 203 cytotoxic, 204 trypsin inhibitor, 205 anticoagulant, 206 advanced glycated end products (AGEs) formation inhibitor, 207 and anti-acute pancreatitis. Proposed mechanism for the sulfamic acid-catalyzed synthesis of 3,3-bis(indol-3yl)indolin-2-ones (77) 6-Aminouracil and its derivatives play a key structural part in numerous natural and synthetic bioactive compounds, and also regarded as a versatile building block for several nitrogen-containing heterocycles possessing a wide range of pharmacological potentials.…”
Section: Scheme 27 Synthesis Of Substituted Alkenes 76 Via Knoevenagmentioning
confidence: 99%
“…(synonyms: L. alba , L. spinosa ; also known as henna or mhendi ; family: Lythraceae), different parts of which have been traditionally used all over the world as cosmetics (hair dye, body paint and tattoo dye) and herbal remedies in treating various ailments . This phenolic quinone compound has been evaluated to possess a wide range of biological and pharmacological activities such as antioxidant, antibacterial, antifungal, cytotoxic, trypsin inhibitor, anticoagulant, advanced glycation end products (AGEs) formation inhibitor, and anti‐acute pancreatitis . The interesting structural pattern of lawsone coupled with its so‐called multifaceted pharmacological potential has motivated chemists to explore this useful scaffold in certain chemical processes, particularly in synthesizing ligands for metal complexation, and a few of its derivatives have already been reported to exhibit a number of biological activities …”
Section: Designing Organic Transformations At Ambient Conditionsmentioning
confidence: 99%